Hubungan Belanja Pemerintah Sektor Pendidikan dan Kesehatan dengan Pertumbuhan Ekonomi: di Provinsi Jawa Barat - Teguh Dwiarsyah (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2026)
This study aims to analyze the effect of government expenditure in the education and health sectors on economic growth across 27 Regencies and Cities in West Java Province. West Java serves as a crucial research locus due to its status as the most populous province and a national industrial hub, despite experiencing economic fluctuations caused by the Covid-19 pandemic. The study utilizes panel data from 27 administrative regions spanning the period 2019 to 2025. The analytical method employed is panel data regression, with the Fixed Effect Model (FEM) selected as the best-fitting model. Statistical results indicate that government expenditure in the education sector has a significant effect on economic growth, as evidenced by a probability value of 0.0035 (< 0.05). However, the negative coefficient suggests that in the short term, education spending acts as a fiscal burden or has not yet yielded immediate returns. Conversely, health sector expenditure does not significantly influence economic growth (probability value 0.4642 > 0.05). This is attributed to health allocations being predominantly curative and maintenance-oriented post-pandemic, thereby failing to generate a rapid multiplier effect. Simultaneously, the independent variables explain 18.6% of the variance in West Java's economic growth.